2015
DOI: 10.1186/s12889-015-2428-4
|View full text |Cite
|
Sign up to set email alerts
|

Six-months follow-up of a cluster randomized trial of school-based smoking prevention education programs in Aceh, Indonesia

Abstract: BackgroundSmoking prevention programs have been taught in schools to reduce the high smoking prevalence and its related problems among adolescent populations. Although short-term benefits have been observed, the long-term effectiveness of such programs appear to be inconsistent. This study aims at investigating the long-term impact of both health and Islamic focused interventions amongst students in Indonesia.MethodsAt 6 months after completion of the interventions, 427 of the original 447 participants (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Apart from recent data on the overall prevalence of adolescent cigarette smoking in Indonesia [12], there is literature reporting prevalence rates in selected districts or provinces, but these findings are based on older data and they do not compare the situation between provinces [25,26,30]. This study found that smoking prevalence was higher among adolescents on Java Island, a pattern reported in a study of smoking among individuals aged 15 years and above from the same survey (the highest smoking prevalence was in West Java Province [32.7%] and the lowest was in Papua [21.9%]) [29], suggesting that adolescent and adult smoking patterns match.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from recent data on the overall prevalence of adolescent cigarette smoking in Indonesia [12], there is literature reporting prevalence rates in selected districts or provinces, but these findings are based on older data and they do not compare the situation between provinces [25,26,30]. This study found that smoking prevalence was higher among adolescents on Java Island, a pattern reported in a study of smoking among individuals aged 15 years and above from the same survey (the highest smoking prevalence was in West Java Province [32.7%] and the lowest was in Papua [21.9%]) [29], suggesting that adolescent and adult smoking patterns match.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies occurred in schools or primary care settings rather than in the workplace [34][35][36]. Similarly, some school-based intervention studies also found significant effects on changing both smoking-related knowledge and attitudes [34,35]. Other school-based intervention studies reported [36] that despite smoking knowledge increasing substantially over the follow-up, the attitudes did not change, mainly because attitudes were more stable than knowledge and more resistant to change.…”
Section: Smoking-related Knowledge and Attitudesmentioning
confidence: 98%
“…Smoking knowledge and attitudes scores were often used as parameters of intervention effectiveness. However, most of these studies occurred in schools or primary care settings rather than in the workplace [34][35][36]. Similarly, some school-based intervention studies also found significant effects on changing both smoking-related knowledge and attitudes [34,35].…”
Section: Smoking-related Knowledge and Attitudesmentioning
confidence: 99%
“…Such programs increase smoking knowledge and critical attitude, and reduce smoking intention; more specifically, school-based smoking prevention programs have been found to be effective for increasing health knowledge and promoting a critical attitude in relation to smoking, and decreasing smoking intention and behaviors in both the short and long term [30]. In addition, adolescents spend most of their week days at school and tend to learn health promotion behaviors from school health providers.…”
Section: Discussionmentioning
confidence: 99%